Manufactured exports and FDI in the MED-11 countries: Recent evolution, determinants and prospects - Khalid Sekkat (Center for Social and Economic Research (CASE), 2012)
This paper investigates the evolution and determinants of manufactured exports and FDI in MED-11 countries over the period 1985-2009 as well as the prospects of their evolution under different scenarios pertaining to the evolution of the determinants. The econometric analysis confirmed the role of exchange rate depreciation, the openness of the economy and the quality of institution and infrastructure in fostering manufactured exports and FDI inflows in the Region. The prospects' assessment suggested that a scenario of deeper integration with the EU entails superior performance regarding manufactured exports and FDI than status quo or less integration with the EU but greater regional integration.
Keywords: F15; F21; O43; 330; Manufactured Exports; FDI; Institutions; MENA; Außenhandel mit Industriegütern; Auslandsinvestition; Internationale Wirtschaftsbeziehungen; Westasien; Nordafrika; Mittelmeerraum